Utilisation of alum sludge ash in mortar production - Ng, Yee Leng (2019)
Alum sludge (AS) is a by-product of water treatment plants that uses aluminium salts as a primary coagulant. It is the most widely generated water treatment sludge worldwide. The disposal of alum sludge into landfills has became an environmental issue due to the enormous quantities generated and the associated costs of disposal to landfill. Meanwhile, the production of cement mortar is very energy and resources intensive. Therefore, this study aims to incorporate alum sludge ash (ASA) as a substitute to cement in mortar production, as it is a negative cost waste while contributing to sustainable development of building materials. In addition to ASA, ground granulated blast furnace slag (GGBFS) was also used as an additional binder to enhance the strength of the mortar. The study includes the investigation the effect of ASA incorporation on the physical, chemical, mechanical and durability properties of mortar. In this study, ten types of composite mortars are prepared, namely M-CTR, M-2ASA, M-4ASA, M-6ASA, M-2GGBFS, M-4GGBFS, M-6GGBFS, M-2ASA 4GGBFS, M-4ASA 4GGBFS and M-6ASA 4GGBFS. All the tests are conducted based on the BS EN 196-3, BS EN 12390-3, BS EN 1015 and BS 1881-122 standards. Life Cycle Assessment (LCA) was also conducted to check on the feasibility of using alum sludge ash to partially replace cement in mortar production. The laboratory results showed that the incorporation of ASA as a substitute to cement in the mortar production deteriorated its mechanical properties but its durability properties are improved.